The transgressive infill of an inherited-valley system: The Springhill Formation (lower Cretaceous) in southern Austral Basin, Argentina - Schwarz, Ernesto (2011)
The Berriasian-Valanginian Springhill Formation of the Austral Basin of southern South America comprises fluvial to marine deposits. In order to interpret depositional systems and unravel the stratigraphic architecture of this unit in the southern region of the basin (Tierra del Fuego Province, Argentina), 500 m of cores combined with well-log data from 41 wells were studied. Facies associations corresponding to fluvial (A1-A6), estuarine (B1-B5) and open-marine (C1-C4) depositional environments were identified. These facies associations succeed each other vertically across the entire study area (6800 km2) forming a ~120-m-thick transgressive succession. This unit filled a north-south-oriented valley system, developed in the underlying Jurassic volcanic complex.Lowstand fluvial deposits of the first stage of the valley-system fill occur in downdip segments of the system above a sequence boundary (SB). These fluvial deposits are overlain by coastal-plain and tide-dominated estuarine strata across an initial transgressive surface (ITS). In the northern sector the earliest valley infill is characterized by a transgressive fluvial succession, overlying a merged SB/ITS that is probably time-equivalent of marginal-marine deposits of the southern sector. The fluvial strata in the north are overlain by wave-dominated estuarine deposits. A drastic change to open-marine conditions is marked by a marine flooding surface, with local evidence of marine erosion (FS-RS). Open-marine strata are thin (<10 m) and dominated by lower-shoreface and offshore-transition deposits. They are capped by a younger flooding surface (FS), which represents the onset to offshore conditions across the study area due to a continuous long-term transgression that persisted until the Barremian.Although the interpreted depositional systems and stratigraphic architecture of the Springhill Formation resemble transgressive incised-valley-fill successions, the greater thickness and larger size of the Springhill valleys suggest inherited rift topography rather than valley development during a relative sea-level fall. © 2010 Elsevier Ltd.